EKSISTENSI HUKUM HINDU DALAM HUKUM ADAT DI TENGAH PERUBAHAN SOSIAL DI DESA ADAT BANJAR TANGGAHAN PEKEN DESA SULAHAN KECAMATAN SUSUT KABUPATEN BANGLI - i gede januariawan (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Hindu Law and Customary Law in Bali are very closely related, so that it often creates confusion about which understanding is Hindu Law and which is Customary Law. During the Raad Kerta period, Van den Berg's theory of receptio in complexu stated,